Implementation of dormitory management at Islamic Center Islamic Boarding School bin Baz Yogyakarta - Qiyadah Robbaniyah; Azima Ummu Magfirotul Taliah; Khonsa (At Turots: Jurnal Pendidikan Islam, 2023)
Educational institutions can develop quickly, a necessity without a system being built. The Bin Baz Islamic Center Islamic Boarding School is a boarding school that has been active in the world of education for a long time and has branches spread across Indonesia, so researchers are interested in researching the Implementation of Dormitory Management at the ICBB Yogyakarta Islamic Boarding School. This research is a qualitative research with phenomenology, interview data collection, observation and documentation. The results of this study are that the facilities provided by the ICBB boarding school are sufficient to support a large number of students. The facilities include dormitories, mosque, kitchen and dining room, basketball court, etc. Efforts made in organizing dormitories are by dividing tasks together with the provisions of the criteria that apply; the pesantren section, the Tarbiyah section, the lughah section, and the tahfidz section. While the dormitory coordinators are taken by ustadzahs who are competent in the field of parenting. The activity agenda that is carried out every year is to form an organization in the hostel called the OSMA section of the hostel, which consists of several sections such as cleanliness, tarbiyah or guidance, language, security, skills, sports, worship, etc. In managing the Pondok ICBB hostel, it also tries to carry out regular monitoring and evaluation on a daily, weekly, monthly and yearly basis. From the results of the evaluation of violations committed by female students such as bullying, theft, running away from the hut or dating, the management will receive an evaluation by providing guidance so that sanction measures have also been carried out with the female guardian if it has entered the category of serious violations. After the evaluation, the ICBB Pondok also continues to try to update programs and regulations, based on outside knowledge that can be applied in the ICBB Pondok.